Telecommunications system reliability engineering, theory, and practice - Ayers, Mark L. (Hoboken, N.J. : Wiley, 2012)
"Increasing system complexity require new, more sophisticated tools for system modeling and metric calculation. Bringing the field up to date, this book provides telecommunications engineers with practical tools for analyzing, calculating, and reporting availability, reliability, and maintainability metrics. It gives the background in system reliability theory and covers in-depth applications in fiber optic networks, microwave networks, satellite networks, power systems, and facilities management. Computer programming tools for simulating the approaches presented, using the Matlab software suite, are also provided"--
Reliability Theory -- Fiber-Optic Networks -- Microwave Networks -- Satellite Networks -- Mobile Wireless Networks -- Telecommunications Facilities -- Software and Firmware.
Includes bibliographical references (pages 227-228) and index.
Print version record.
Keywords: Telecommunication systems; TECHNOLOGY & ENGINEERING -- Electronics -- General; TECHNOLOGY & ENGINEERING -- Telecommunications; Telecommunication systems; Electronic books